Answer:
A. 77.4
Step-by-step explanation:
<u>Linear approximation formula</u>
![L(x)=f(a)+f'(a)(x-a)](https://tex.z-dn.net/?f=L%28x%29%3Df%28a%29%2Bf%27%28a%29%28x-a%29)
Given function:
![f(x)=(x+1)^2](https://tex.z-dn.net/?f=f%28x%29%3D%28x%2B1%29%5E2)
![\boxed{\begin{minipage}{5.4 cm}\underline{Chain Rule for Differentiation}\\\\If $y=f(u)$ and $u=g(x)$ then:\\\\$\dfrac{\text{d}y}{\text{d}x}=\dfrac{\text{d}y}{\text{d}u}\times \dfrac{\text{d}u}{\text{d}x}$\\\end{minipage}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cbegin%7Bminipage%7D%7B5.4%20cm%7D%5Cunderline%7BChain%20Rule%20for%20Differentiation%7D%5C%5C%5C%5CIf%20%20%24y%3Df%28u%29%24%20%20and%20%20%24u%3Dg%28x%29%24%20%20then%3A%5C%5C%5C%5C%24%5Cdfrac%7B%5Ctext%7Bd%7Dy%7D%7B%5Ctext%7Bd%7Dx%7D%3D%5Cdfrac%7B%5Ctext%7Bd%7Dy%7D%7B%5Ctext%7Bd%7Du%7D%5Ctimes%20%5Cdfrac%7B%5Ctext%7Bd%7Du%7D%7B%5Ctext%7Bd%7Dx%7D%24%5C%5C%5Cend%7Bminipage%7D%7D)
![\boxed{\begin{minipage}{5 cm}\underline{Differentiating $x^n$}\\\\If $y=x^n$, then $\dfrac{\text{d}y}{\text{d}x}=xn^{n-1}$\\\end{minipage}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cbegin%7Bminipage%7D%7B5%20cm%7D%5Cunderline%7BDifferentiating%20%24x%5En%24%7D%5C%5C%5C%5CIf%20%20%24y%3Dx%5En%24%2C%20then%20%24%5Cdfrac%7B%5Ctext%7Bd%7Dy%7D%7B%5Ctext%7Bd%7Dx%7D%3Dxn%5E%7Bn-1%7D%24%5C%5C%5Cend%7Bminipage%7D%7D)
![\boxed{\begin{minipage}{4 cm}\underline{Differentiating $ax$}\\\\If $y=ax$, then $\dfrac{\text{d}y}{\text{d}x}=a$\\\end{minipage}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cbegin%7Bminipage%7D%7B4%20cm%7D%5Cunderline%7BDifferentiating%20%24ax%24%7D%5C%5C%5C%5CIf%20%20%24y%3Dax%24%2C%20then%20%24%5Cdfrac%7B%5Ctext%7Bd%7Dy%7D%7B%5Ctext%7Bd%7Dx%7D%3Da%24%5C%5C%5Cend%7Bminipage%7D%7D)
Use the chain rule to differentiate the function.
![\textsf{Let }\:y=u^2\:\textsf{ where }u=(x+1)](https://tex.z-dn.net/?f=%5Ctextsf%7BLet%20%7D%5C%3Ay%3Du%5E2%5C%3A%5Ctextsf%7B%20where%20%7Du%3D%28x%2B1%29)
Differentiate the two parts separately:
![y=u^2 \implies \dfrac{\text{d}y}{\text{d}u}=2u](https://tex.z-dn.net/?f=y%3Du%5E2%20%5Cimplies%20%5Cdfrac%7B%5Ctext%7Bd%7Dy%7D%7B%5Ctext%7Bd%7Du%7D%3D2u)
![u=x+1 \implies \dfrac{\text{d}u}{\text{d}x}=1](https://tex.z-dn.net/?f=u%3Dx%2B1%20%5Cimplies%20%5Cdfrac%7B%5Ctext%7Bd%7Du%7D%7B%5Ctext%7Bd%7Dx%7D%3D1)
Put everything back into the chain rule formula:
![\begin{aligned} \implies \dfrac{\text{d}y}{\text{d}x} & =2u \times 1\\ & = 2u \\ & = 2(x+1)\\ & = 2x+2 \end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%20%5Cimplies%20%5Cdfrac%7B%5Ctext%7Bd%7Dy%7D%7B%5Ctext%7Bd%7Dx%7D%20%26%20%3D2u%20%5Ctimes%201%5C%5C%20%26%20%3D%202u%20%5C%5C%20%26%20%3D%202%28x%2B1%29%5C%5C%20%26%20%3D%202x%2B2%20%5Cend%7Baligned%7D)
.
The <u>linear approximation</u> at a = 8 is:
![\begin{aligned}L(x) & =f(a)+f'(a)(x-a)\\\\\implies L(x) & = f(8)+f'(8)(x-8)\\& = (8+1)^2+(2(8)+2)(x-8)\\& = 81+18(x-8)\\& = 18x-63\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7DL%28x%29%20%26%20%3Df%28a%29%2Bf%27%28a%29%28x-a%29%5C%5C%5C%5C%5Cimplies%20L%28x%29%20%26%20%3D%20f%288%29%2Bf%27%288%29%28x-8%29%5C%5C%26%20%3D%20%288%2B1%29%5E2%2B%282%288%29%2B2%29%28x-8%29%5C%5C%26%20%3D%2081%2B18%28x-8%29%5C%5C%26%20%3D%2018x-63%5Cend%7Baligned%7D)
Finally, substitute x = 7.8 into the <u>linear approximation equation</u>:
![\begin{aligned}\implies L(7.8) & =18(7.8)-63\\& = 140.4-63\\& = 77.4\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%5Cimplies%20L%287.8%29%20%26%20%3D18%287.8%29-63%5C%5C%26%20%3D%20140.4-63%5C%5C%26%20%3D%2077.4%5Cend%7Baligned%7D)
Answer:
the equation in slope-intercept form
<u>y=(0).x+2</u>
slope = 0
y-intercept = 2
Step-by-step explanation:
![y=2](https://tex.z-dn.net/?f=y%3D2)
the equation in slope-intercept form
![y=(0).x+2](https://tex.z-dn.net/?f=y%3D%280%29.x%2B2)
but,
![y=mx+c](https://tex.z-dn.net/?f=y%3Dmx%2Bc)
m= slope
c= y intercept
therefore,
slope = 0
y-intercept = 2